Gene cloning and recombinant protein expression of lipase from marine bacterium - Noh, Laila (2014)
Nowadays salt tolerant enzymes have gained attention since they have advantages in food processing industries and pharmaceutical field. Marine microbes represent a potential source of bioactive compounds. Many reported studies only showed detection of lipase enzymes in marine bacteria instead of cloning and characterize the enzymes. The aim of this study was to isolate, clone and express lipase from a marine bacterium. The halophilic bacteria were isolated from seawater sample which collected from Tanjung Pelepas, Johor. All of the twenty seven putative lipase producing bacteria were screened for lipase production quantitative and qualitatively. Isolate J15 was selected for further study on the basis of lipase activity and novelty of the strain. The isolate J15 is a Gram negative bacterium with the ability to produce 0.096 U/ml of lipase activity extracellularly. Analysis of 16S rDNA revealed that it shows 97% identity to type strain Photobacterium jeanii . Lipase gene from Photobacterium sp. strainJ15 strain was isolated by using PCR amplification method with the closest homologous lipase being M37 lipase of Photobacterium lipolyticum sp. nov. with 83 % identity. The G+C content between the isolate and P. lipolyticum are 42.72 and 41.48 %, respectively. Phylogenetic analysis indicated that J15 lipase contained GHSKG as conserved pentapeptide and it clustered with the lipolytic enzymes from class III lipase with catalytic triad (Ser, Asp, and His). J15 lipase show rare oxyanion hole, (RG) normally found in filamentous fungi. Further analysis was carried out by cloning the J15 lipase gene into an expression vector, peT32b(+) plasmid and transformed into RosettaGamiB(DE3)pLysS. Under the strong T7 promoter, functioning recombinant J15 lipase was synthesized. The open reading frame of J15 lipase was 1023 bp in length encoding an open reading frame containing 341 amino acid residues with a predicted molecular weight of approximately 38 kDa and pI 6.5. Total size of J15 lipase including fusion protein was about 55 kDa. Optimum recombinant lipase expression (18.4 U/ml) was observed when induced the recombinant strain with 0.05 mM IPTG at 30 oC after 16 h of incubation. Crude enzyme of recombinant J15 was purified through Nickel-sepharose affinity chromatography obtaining 22.97 U/mg specific lipase activity with 5.39 fold and 97.79 % of recovery. Characterization of recombinant J15 lipase showed highest substrate specificity for long carbon chain of triglycerides, triolein (C18:1) and long carbon chain of natural oil, coconut oil (C12). In addition, the recombinant displayed activity at pH 5-9 and temperature 15-55 oC in ranges and stable in the presence of 11 % NaCl. The recombinant J15 lipase showed total inhibition with the presence of EDTA and partially affected by reducing agents (dithiothreitol (DTT) and β-mercaptoethanol). J15 lipase was classified into Photobacterium sp. with mesophilic characteristics. The moderate halophile lipase enzyme was successfully isolated, cloned and expressed. The purification of recombinant J15 lipase produced functioning salt tolerant protein with high recovery in a single step purification system. Further analysis of this lipase could bring to better understanding on its structural and function.